TESTICULAR DEVELOPMENT AND SEMINAL ATTRIBUTES OF AGONDA GOAN PIG - CHAKURKAR, EB; NAYAKVADI, S; NAIK, PK; MANDAL, A; KARUNAKARAN, M (The Indian Journal of Animal Reproduction, 2022)
Out of thirty-six male Agonda Goan pigs (age, 30-270 d), six males were castrated at a time in a 30 d interval starting from 30 d to 180 d to study the biometry of testis and epididymis, whereas, six males were left uncastrated for semen studies. Testicular length, width, thickness, circumference, weight and epididymal weight were increased (p
Keywords: Agonda Goan; Pig; Puberty; Seminal attributes; Testosterone